Enhancing effectiveness of employees through training and development in the health care department of Khyber Pakhtunkhwa Pakistan: A Literature Review - Hussain, Altaf; Yusoff, Rosman Md; Banoori, Sajjad Ahmad; Khan, Anwar; Khan, Muhammad Asad (International Review of Management and Marketing, 2016)
This paper is mainly concerned with improving the effectiveness of training and development within health department of provincial govt. Pakistan. For this purpose training and development practices in both developing and developed countries have been explored through the review of published literature. Based on literature review, this paper has to discuss the effectiveness of training and development program through primary research based on semi structured interviews and questionnaire in the concerned department. The findings clearly revealed that training and development approach is not systematic at all with a view of just a formality in the concerned department and the main barriers appeared to be organizational environment and the political intervention. On the basis of the findings and discussion, conclusion has been drawn and recommendations have been made to adopt the training and development model presented in the literature review which is necessary to improve employee effectiveness through such programmes for strategic impact. Towards the end of the paper, future research design has been discussed briefly together with future research opportunities in the same field. Keywords: Training and development, employees, effectiveness, health department JEL Classification: M000